Analis Pelanggaran Etika Hukum Bisnis dalam Penanganan Kredit Macet terhadap Nasabah Prioritas - Agree Dani Norrochman; Halimah Zahrah; Amanda Helinkika; Shellvy Setiawan (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The Indonesian banking industry is facing increasing complexity in implementing business ethics and legal compliance, especially in handling non-performing loans (NPL) involving priority customers. This study aims to analyze the violations of business legal ethics in the handling of NPL cases and their impact on customers and the banking industry. Using a qualitative method with a normative-descriptive literature review approach, this study analyzes data from academic journals, regulations, and media reports published between 2023 and 2025. The findings indicate significant ethical violations, including lack of transparency in debt collection procedures, unequal treatment in credit restructuring, and aggressive collection practices that infringe on consumer rights. These actions not only harm customers psychologically and reputationally but also damage public trust and threaten regulatory stability in the banking sector. The study recommends comprehensive improvements involving banks, regulators, and society to uphold ethical business practices that ensure fairness, accountability, and consumer protection in banking operations.